Compensation of the nonlinear impairments in all-optical OFDM systems based on the optical phase conjugation (OPC) module - Azarnia, A.; Sahbudin, R. K. Z.; Adzir, M.; Anas, S. B. A. (INSIGHT - Indonesian Society for Knowledge and Human Development, 2022)
This study presents a nonlinearity mitigation technique for achieving high performance in the All-Optical Orthogonal Frequency Division Multiplexing (AO-OFDM) transmission systems. Therefore, the Optical Phase Conjugation (OPC) technique has been employed for mitigating the Nonlinear Phase Noise (NLPN) in the AO-OFDM transmission systems. The NLPN has been mitigated in the AO-OFDM transmission system by utilizing the proposed OPC at the middle point of the transmission link. The proposed system is numerically simulated by Virtual Photonics Integrated (VPI) Transmission Maker 9.0 at a symbol rate of 25 Gsymbol/s. During the simulation, 29 subcarriers were generated by Optical Frequency Comb Generator (OFCG) and modulated by 4-array Quadrature Amplitude Modulator (4-QAM). The generated signals are transmitted over 580 km fiber link and received by the coherent receiver. The transmission link contains 4 spans before and 4 spans after OPC module. Each span comprises the Standard Single-Mode Fiber (SSMF) and an EDFA (noise figure = 6 dB) to compensate for the fiber loss. The length of each span is fixed at 70 km in the system simulation. In addition, a 20 km Dispersion Compensation Fiber (DCF) has been used just before the OPC module to compensate for accumulated fiber dispersion. The Signal-to-Noise Ratio (SNR) and Error Vector Magnitude (EVM) have been used to certify the feasibility of the proposed technique. The results reveal that by employing the proposed OPC module, the SNR is improved by ~3.4 dB, and the EVMs are substantially reduced.